Pemberdayaan Kader Kesehatan Melalui Penyuluhan Kesehatan Tentang Golden Age Period For Golden Generation di Wilayah Puskesmas Talun Kabupaten Cirebon - Sumarmi Sumarmi; Erida Fadila; Titi Sri Suyanti (Lembaga Pengembangan Kinerja Dosen, 2025)
The golden period or Golden age period is the initial stage where the child's brain experiences growth and develops rapidly and quickly absorbs the information provided. This golden period is the most important in the early cycle of a child's life. The golden period in children is the most important period in which the child's brain or intelligence develops very rapidly. monitoring a child's Golden Age Period occurs in the first thousand days of life which is calculated from the age in the womb until the child is three years old. The purpose of community service activities is to provide knowledge to the community: health cadres, mothers of babies/toddlers, and families about the importance of the golden age growth. Community service activities carried out by the method of transferring knowledge through counseling and training to health cadres